Potential Bioactive Compounds of Plant as Anticancers in Lung Cancer A549 Cell Line: A Systematic Review - Zulfikri, Elzam Naufal; Ibrahim, Muhammad Hamdi; Elisa, Tasya Putri Pratama; Nelvi, Dennisa Arra; Ilham, Kurniadi; Maliza, Rita (Jurnal Biologi Tropis, 2024)
Cancer is one of the non-communicable diseases of global concern the world. Lung cancer is the leading cause of cancer death worldwide, and is the highest cause of death in both men and women at 18% of the world's 9.9 million cancer deaths. Efforts to prevent and cure cancer include using chemotherapy and anti-cancer drugs. Plants are rich in secondary metabolites which are byproducts of plant metabolism that have proven to be useful for the discovery and development of many medicines’ discovery and development of medicines. This article aims to review the potential of plant bioactive compounds that play a role in anticancer activity in lung cancer A549 cell line. In this journal review we used PubMed Centre database to identify articles published between 2014 and 2024. 10 studies were obtained from keywords concerning extracts bioactive compounds of plants used as lung anticancer against A549 cell line. From the results obtained, it was reported that plants containing active compounds such as polyphenols, terpenoids (oleanolic acid, ursolic acid, betulinate, ferruginol), flavonoids (tiliroside), and alkaloids can act as anticancer agents and are proven to inhibit the growth of lung cancer A549 cell line.